2012
DOI: 10.1038/nature11496
|View full text |Cite
|
Sign up to set email alerts
|

Clonal allelic predetermination of immunoglobulin-κ rearrangement

Abstract: Although most genes are expressed biallelically, a number of key genomic sites--including immune and olfactory receptor regions--are controlled monoallelically in a stochastic manner, with some cells expressing the maternal allele and others the paternal allele in the target tissue. Very little is known about how this phenomenon is regulated and programmed during development. Here, using mouse immunoglobulin-κ (Igκ) as a model system, we demonstrate that although individual haematopoietic stem cells are charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 35 publications
3
53
0
Order By: Relevance
“…To understand how this comes about, we followed the kinetics of this process for one individual clone (clone 4). Previous studies in our laboratory have already shown that the two alleles in pre-B cells are differentially marked by replication timing and J-Cκ accessibility, and that it is always the early allele which is preferentially rearranged in the initial recombination step1221. In keeping with this, analysis after only 12 h of induction indicated that the vast majority of rearrangement events occurred on the B6 allele, which is indeed early replicating in this particular clone.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…To understand how this comes about, we followed the kinetics of this process for one individual clone (clone 4). Previous studies in our laboratory have already shown that the two alleles in pre-B cells are differentially marked by replication timing and J-Cκ accessibility, and that it is always the early allele which is preferentially rearranged in the initial recombination step1221. In keeping with this, analysis after only 12 h of induction indicated that the vast majority of rearrangement events occurred on the B6 allele, which is indeed early replicating in this particular clone.…”
Section: Resultssupporting
confidence: 66%
“…Previous work in our laboratory, however, has indicated that this is probably not the case and the decision is actually of an instructive nature, with the two alleles first becoming marked by asynchronous replication at the early lymphoid progenitor stage followed later by opening of the κ J–C region specifically on the early allele. Through the use of pre-B-cell clones, it was then demonstrated that it is this same allele that undergoes the first rearrangement in each cell12. The κ locus is distributed over a large 3 Mb region carrying ∼140 different V segments13 and this domain already has an accessible chromatin conformation at the pre-B-cell stage even prior to the initiation of rearrangement141516.…”
mentioning
confidence: 99%
“…These mechanisms exist in other monoallelic gene expression programs and include pre-marking of alleles by histone modifications or asynchronous replication, or feedback that ensures only a single allele is activated 3033 .…”
Section: Resultsmentioning
confidence: 99%
“…BaF3 cell medium was additionally supplemented with IL3 secreted by WEHI-3b cells. IL-7-dependent pre-B cell cultures used for chromatin immunoprecipitation (ChIP) analysis were performed as has been previously described (35). COP8 cells were transiently transfected with a Pax5 expression plasmid (gift from M. Busslinger) using the DEAE dextran method (36).…”
Section: Methodsmentioning
confidence: 99%
“…IL-7-dependent pre-B cell cultures were made from the bone marrow of Igκ WT/ΔDm mice as has been previously described (35). Cells were crosslinked with formaldehyde, chromatin extracted, and immunoprecipitated with an antibody directed against Pax5 (5 μg per 30 μg DNA) (SantaCruz).…”
Section: Methodsmentioning
confidence: 99%